A Japanese language proficiency and business Japanese competence: what do Malaysian Japanese companies expect? - Lee, Su Yeoh; Manjet Kaur Singh, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Malaysian Japanese speaking graduates with Japanese language proficiency (JLP) and business Japanese competence (BJC) employed in Japanese companies (JC) in Malaysia are considered an asset by their employers. However, to what extent are their JLP and BJC sufficient to function in JC is an under researched area and deserves further scrutiny. Therefore, the focus of this research is to identify JC employers’ JLP and BJC requirements of Malaysian Japanese speaking graduates in their Malaysian companies. This qualitative research via semi-structured one-to-one interviews with JC employers of selected companies in Malaysia investigated the requirements of JLP and BJC for Malaysian Japanese speaking graduates employed in JC. The findings revealed that JLP requirement is dependent on position and task whereas time management and business customs, Ho/Ren/So (Reporting / Contacting / Consulting) are considered as important BJC practices. Furthermore, speaking and listening in Japanese language is considered as crucial skills and the most challenging for Malaysian Japanese speaking graduates at JC to master. Incorporating Japanese business customs and workplace practices in Japanese language curriculum at higher education and increasing internship opportunities at JC would ensure Malaysian Japanese speaking graduates acquire the required JLP and BJC through their higher education. This research augurs well for the enhancement of Japanese language curriculum in higher education institutions in Malaysia as well as Japan-Malaysia bilateral trade to further strengthen Japanese companies’ presence in Malaysia and attract new Japanese investments with high level of JLP and BJC manpower.